(untitled) (Ameghiniana, 2016)
Calmoniid trilobites of the “Metacryphaeus tuberculatus group” occur in many Devonian localities within the Malvinokaffric Realm. In the Parnaíba Basin, in northeastern Brazil, the group is represented by Metacryphaeus tuberculatus Kozlowski, 1923, and M. meloi Carvalho, Edgecombe and Lieberman, 1997, from the late Eifelian–early Givetian Pimenteira Formation in the environs of the city of Picos and the early Givetian Passagem Member (Pimenteira Formation) from the vicinities of Picos and Pimenteiras in Piauí State. Based on specimens found in the region of João Costa, southeastern Piauí State, the present study reinforces data on the occurrence of M. tuberculatus in the Pimenteira Formation and reports the presence of genal spines in some individuals of M. meloi, indicating a feature previously unknown for this species. Resumen. EL “GRUPO METACRYPHAEUS TUBERCULATUS” (TRILOBITA, CALMONIIDAE) DEL DEVÓNICO DE LA CUENCA DEL PARNAÍBA, BRASIL. Los trilobites calmónidos del “grupo Metacryphaeus tuberculatus” se producen en diversas localidades del Devónico en el Dominio Malvinocá- frico. En la Cuenca del Parnaíba, en el noreste de Brasil, el grupo está representado por las especies Metacryphaeus tuberculatus Kozlowski, 1923, y M. meloi Carvalho, Edgecombe and Lieberman, 1997, la primera del Eifeliano tardío–Givetiano temprano de la Formación Pimenteira en el área de la ciudad de Picos, y la segunda del Givetiano temprano del Miembro Passagem (Formación Pimenteira), de las proximidades de las ciudades de Picos y Pimenteiras, en el Estado del Piauí. El presente estudio refuerza la presencia de M. tuberculatus en la Formación Pimenteira basado en especímenes encontrados en la región de la ciudad de João Costa, en el sureste del Estado de Piauí, e informa la presencia de espinas genales en algunos individuos de M. meloi, indicando una característica previamente desconocida para esta especie.